PRODUCTION AND CHARACTERIZATION OF A BIODEGRADABLE POLYMER POLY(3-HYDROXYBUTYRIC ACID) FROM GLUCOSE USING Erwinia sp. USMI-20 - Akmal Djamaan; Mohamed Isa Abd. Majid; Mohd. Azizan Mohd. Noor (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2001)
The production and characterization of a biodegradable polymer poly(3-hydroxybutyric acid), P(3HB) from glucose as sole carbon source by Erwinia sp. USMI-20 has been carried out. Results showed that Erwinia sp. USMI-20 could produced P(3HB) with a maximum polymer content of 48 % of the dry cell weight, an amount of polymer of 2.8 g/l, a dry cell weight of 5.8 g/l, a maximum specific growth rate of 0.21 h-1. a maximum polymer production rate of 0.02/h, yield YP(3HB)//C of 0.21 g/g, with the optimum fermentation time of 48 hours. The melting temperature (T) and glass transition temperature (Tg) of the P(3HB) were 175 ˚C and 15 ˚C, respectively. The weigh-average molecular weight (Mw) was in the range of 1,000,000 to 1,120,000 D whereas the number-average molecular weight (Mn) was in the range of 420,000 to 580,000 D with the polydispersity index (Mw,Mn) in range of 1.9 to 2.4. Key word: biodegradable polymer, glucose and Erwina sp.